2008
DOI: 10.1186/1472-6963-8-228
|View full text |Cite
|
Sign up to set email alerts
|

The impact of SARS on hospital performance

Abstract: Background: During the SARS epidemic, healthcare utilization and medical services decreased significantly. However, the long-term impact of SARS on hospital performance needs to be further discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
46
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 15 publications
3
46
0
Order By: Relevance
“…Another study on the impact of SARS on emergency services in Taiwan found similar results to the ones identified for the current Portuguese situation: there was a peak of 51% reduction during the SARS epidemic, and this reduction was observed for all triage categories [16]. Studies produced in the SARS context recommended the development of management strategies to deal either with the re-emergence of SARS or other contagious diseases, taking into consideration both the immediate and the long-term effects of such outbreaks [16, 19].…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Another study on the impact of SARS on emergency services in Taiwan found similar results to the ones identified for the current Portuguese situation: there was a peak of 51% reduction during the SARS epidemic, and this reduction was observed for all triage categories [16]. Studies produced in the SARS context recommended the development of management strategies to deal either with the re-emergence of SARS or other contagious diseases, taking into consideration both the immediate and the long-term effects of such outbreaks [16, 19].…”
Section: Discussionmentioning
confidence: 65%
“…It is not possible to accurately predict future scenarios, but in the short term, an altered behavior is expected given the traditional urgency use. In the study by Chu et al [19], results showed that, although the SARS pandemic period lasted 3 months, the recovery time from previous average levels of use was gradual of 45, 77 and 87% in the years that followed the historical demand.…”
Section: Discussionmentioning
confidence: 99%
“…One of the most impacted populations by COVID-19 is the health care practitioner community [ 43 , 44 ]. During the SARS (severe acute respiratory syndrome) outbreak, health care workers and hospital systems experienced measurable negative psychological impacts [ 45 - 48 ]. Due to the current outbreak, health care practitioners may have experienced a variety of multilevel stressors, such as (1) interruptions in routine job duties and responsibilities, (2) limited knowledge and data, and (3) worries about job security due to decreased patient volumes.…”
Section: Cancer Screening Challenges Opportunities and Solutionsmentioning
confidence: 99%
“…12,13 Observations from previous outbreaks have shown changes in the use of health care services during the outbreak. [14][15][16][17][18] The literature describing the changes in surgical services during outbreaks, including COVID-19, is limited to subjective retrospective evaluations using questionnaires and surveys. [19][20][21][22][23][24] The reported observations from those studies have described increased surgical cancellation rates and a decline in the number of elective cases, on the basis of subjective survey responses from surgeons.…”
Section: Introductionmentioning
confidence: 99%